Gc-Ms Determination Of Bioactive Components Of Eugenia Flocossa Bedd. (Myrtaceae) - MARY JELASTIN KALA, S,; TRESINA SORIS, P,; MOHAN, V.R, (International Journal of Pharma and Bio Sciences, 2012)
In the present study, the bioactive components of Eugenia flocossa leaves have been evaluated using GC-MS. The chemical compounds of the ethanol extract of Eugenia flocossa were investigated using Perkin-Elmer Gas Chromatography- Mass Spectrometry, while the mass spectra of the compounds found in the extract was matched with the National Institute of Standards and Technology (NIST) library. Thirteen compounds were identified. GC-MS analysis of ethanol extracts of Eugenia flocossa revealed the existence of 1, 2, 3- Benzenetriol (Synonyms: Pyrogallol) (26.72%), n-Hexadecanoic acid (23.49%), Oleic acid (13.39%), 3,3-dimethyl- octane (7.90%), 3,7-dimethyl-1-Octanol (Synonyms: Geraniol tetrahydride) (6.11%)- 1,2- Benzenedicarboxylic acid, diisoochyl ester (5.56%), 2-Isopropyl-5-methyl-1-heptanol (4.12%) and tau - Muurolol (3.57%) and α-cadinol (3.37%). This is the first report of identification of active constituents from leaf of Eugenia flocossa Bedd.